Investigating the formation and evolution of plant diversity patterns in the Qiangtang Plateau based on phylofloristics approach - Xiaoping Li; Yun Han; Lei Miao; Hao Xu; Jingya Yu; Shuang Han; Faqi Zhang (Global Ecology and Conservation)
Phylofloristics integrates phylogenetic information into the analysis of flora to elucidate the origin and evolutionary history of flora. The Qiangtang Plateau, located in the hinterland of the Tibetan Plateau, is the ''Roof of the World's Roof,'' serving as a natural laboratory for studying the origin and evolution of cold and arid flora not only within the Tibetan Plateau but also globally. We analyzed the phylogenetic diversity (PD) of the Qiangtang Plateau flora and the effects of environmental factors on the most phylogenetic beta diversity, and inferred the divergence time of species based on a phylogenetic tree constructed from 228 complete plastid genomes, aiming to explore the pattern of plant diversity and its evolutionary history on the Qiangtang Plateau. We quantified the PD of the Qiangtang Plateau flora utilizing a macro-phylogenetic tree derived from a plant list of 370 species. Our analysis identified two distinct phyloregions, designated CⅠ and CⅡ, corresponding to the southeastern and northwestern sectors of the plateau, respectively, as delineated by their beta diversity. Concurrently, our findings indicate that the primary climatic determinants of phylogenetic beta diversity in these regions are bio15 (precipitation seasonality) and bio17 (precipitation in the driest quarter). Furthermore, using fossil data, we deduced that the emergence of seed plant families in this region dates back to the Cretaceous period (145.00 Ma), with a significant acceleration in evolutionary rates observed since the onset of the Quaternary Ice Age (2.00 Ma). These findings underscore the pivotal role of the uplift of the Qiangtang Plateau and the climatic shifts during the Quaternary Ice Age as primary drivers shaping the region's contemporary distribution patterns of alpine plants.